Minat Beli Produk Private Label pada Alfamidi Kuala Simpang - Dewi Rosa Indah; Suri Amalia; muhammad Ikbal; Zenitha Maulida (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
This study was conducted with the aim of knowing the factors that influence the purchase intention of Alfamidi's private label products. The study used a sample of 96 respondents who were consumers of Alfamidi's private label products. Methods of data analysis using multiple linear regression equation, test the coefficient of determination (R2), test the hypothesis (t and F test). The results of the multiple linear regression equation show that price and product quality have a positive effect on buying interest while risk perception has a negative effect on buying interest. The results of the t test show that partially the price has a significant effect on buying interest, product quality partially has a significant effect on buying interest while risk perception partially has no significant effect on buying interest. The results of the F test show that simultaneously price, product quality and risk perception have a significant effect on buying interest. The results of the determination coefficient test (R2) of 0.402 or 40.2% that the price, product quality and risk perception variables can explain the interest in buying Alfamidi's private label products and the remaining 59.8% is influenced by other variables not examined such as promotion and distribution.